A Case of Pathological Complete Response Following FOLFIRINOX Therapy for Pancreatic Adenocarcinoma with Synchronous Distant Lymph Node Metastases - Tsujie, Masanori (Int J Surg Case Rep, 2020)
INTRODUCTION: We report a case of conversion surgery for pancreatic ductal adenocarcinoma (PDAC) with synchronous distant metastases showing pathological complete response (pCR) after FOLFIRINOX therapy. PRESENTATION OF CASE: A 46-year-old woman with obstructive jaundice was referred to our hospital. A CT scan revealed a hypo-vascular mass in the head of the pancreas with multiple para-aortic lymph nodes and a Virchow’s node swollen. The serum CA 19-9 level was 71795.1 U/mL. The result of tumor biopsy from the biliary stenotic site was concordant with adenocarcinoma. She was diagnosed with PDAC with distant metastases. After 10 courses of FOLFIRINOX followed by 4 courses of FOLFIRI, a CT scan showed that distant lymph node swellings disappeared, and CA19-9 level became almost normal. She underwent pancreaticoduodenectomy with dissection of para-aortic lymph nodes 8 months after the initiation of chemotherapy. Pathologically, no evidence of residual adenocarcinoma was observed in neither pancreas nor lymph nodes. Adjuvant chemotherapy using S-1 was administered for 6 months, and no recurrence has been observed 4 years after surgery. BRCA1/2 mutations were not detected in patient’s DNA. DISCUSSION: With the induction of intensive chemotherapies such as FOLFIRINOX, an increasing number of patients with synchronous distant metastases could become suitable candidates for surgery of the primary lesion because of the potential complete response of metastatic lesions. CONCLUSION: This case presented a rare occurrence of pCR in a patient with unresectable PDAC with distant metastases who received FOLFIRINOX. The feasibility and benefits of conversion surgery in such patients must be investigated in future trials.